2018
DOI: 10.1007/s40290-018-0223-0
|View full text |Cite
|
Sign up to set email alerts
|

International Comparison of Five Herbal Medicine Registration Systems to Inform Regulation Development: United Kingdom, Germany, United States of America, United Arab Emirates and Kingdom of Bahrain

Abstract: BackgroundHerbal medicine (HM) regulation is less developed than that of allopathic medicines, with some countries lacking specific regulations.ObjectiveFor the purpose of informing a registration system for HMs in Kuwait, which does not manufacture but imports all HMs, this study compared the similarities and differences between the current HM registration systems of five countries.MethodsThe five countries were selected as major source countries of HM in Kuwait (United Kingdom (UK), Germany and United States… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 18 publications
0
38
0
1
Order By: Relevance
“…Findings from comparing the HM registration laws in five countries (1) revealed that all comparative authorities state in their HMs definitions that the product must consist of plant materials, with Germany, UK (under European Union Directive 2004/24/EC), Bahrain and UAE having the highest similarity in defining a HM. These four countries' definitions are consistent with the recommended World Health Organization (WHO) definition of an "authorized industrially manufactured therapeutic herbal product for registration" (13).…”
Section: The Recommendations Proposed Definition and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from comparing the HM registration laws in five countries (1) revealed that all comparative authorities state in their HMs definitions that the product must consist of plant materials, with Germany, UK (under European Union Directive 2004/24/EC), Bahrain and UAE having the highest similarity in defining a HM. These four countries' definitions are consistent with the recommended World Health Organization (WHO) definition of an "authorized industrially manufactured therapeutic herbal product for registration" (13).…”
Section: The Recommendations Proposed Definition and Classificationmentioning
confidence: 99%
“…Herbal medicines (HMs) have been defined as "preparations manufactured industrially consisting of active ingredient(s) which is/are purely and naturally original, not chemically altered plant substance(s), and is/are responsible for the overall therapeutic effect of the product" (1). Due to a belief that as "natural" products, HMs are "safe" or "safer" than conventional medicines, consumers have turned to plant-derived preparations (2).…”
Section: Introductionmentioning
confidence: 99%
“…The MCA differentiated a product as medicine or food or cosmetics based on the product claims and had to comply as the Directive 65/65/EEC way back in 1995. (Alostad et al, 2018).…”
Section: United Kingdom (Uk)mentioning
confidence: 99%
“…Companies which opt to register under the THR scheme will have to provide evidence of quality as per the GMP standards and evidence of safety and ef icacy based on long traditional use of 30 years overall and 15 years in EU, the label should carry that the THR certi ication mark and a statement that the product is "exclusively based on long term use". For major health claims, or the products that calls for a medical prescription, a market authorisation is required, and in addition to the above requirements, clinical studies, along with toxicological studies are to be provided (Alostad et al, 2018).…”
Section: United Kingdom (Uk)mentioning
confidence: 99%
“…In SJS patients suspected of suffering from herbal medicine-induced etiology, it is very difficult to identify the specific medicine causing the hypersensitivity because most patients consume a mixture of herbal medicines. 11,[17][18][19][20][21] A diagnosis of herbal medicine-induced SJS in HIVpatients is reported here in addition to a literature-based description of SJS related to the characteristics and criteria used in both its diagnosis and oral treatment.…”
Section: Dental Journal (Majalah Kedokteran Gigi)mentioning
confidence: 99%